Analysis of High School Needs for the Development of Virtual Laboratories Based On Augmented Reality Technology on Acids and Bases Materials - Rusdi, Hikmah; Sugiarti, Sugiarti; Husain, Halimah (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Limited laboratory facilities in high schools remain the main obstacle in chemistry learning, especially in acids and bases material that requires direct experimentation to reinforce concepts. Augmented reality (AR) technology through virtual laboratories offers an innovative alternative that enables safe, interactive, and flexible practicum simulations. This study aims to analyze the needs of teachers and students for the development of AR-based virtual laboratories and identify the challenges of its implementation. The research method was qualitative with a needs analysis approach, involving in-depth interviews, observation, and curriculum document analysis at six high schools in Indonesia. The results show that more than 80% of teachers reported that limited laboratory facilities and safety risks are the main reasons for the difficulty of conducting acids and bases practicum in schools. As much as 85% of students stated that lecture-based learning alone makes acid–base concepts feel abstract and difficult to understand. Needs analysis indicated that teachers expect AR-based virtual laboratories to feature realistic acid–base experiment simulations, equipped with 3D animations of ionic reactions, digital pH indicators, and quiz-based evaluation features. Meanwhile, students emphasized the importance of appealing design, simple navigation, and compatibility with smartphones and offline access. The study also found main challenges including limited ICT devices in schools, low digital literacy among teachers, and the need for intensive training to support AR technology implementation in chemistry learning. These findings complement previous research focused on media design by presenting the real needs of users in the field. Theoretically, this study enriches the literature on AR utilization in science education through the integration of user needs analysis. Practically, the results can serve as a reference for media developers, teachers, and policymakers in designing AR-based virtual laboratories that are relevant, effective, and inclusive, thereby improving the quality of high school chemistry learning on acids and bases material.